Outcome of severe unilateral cerebellar hypoplasia - Poretti, Andrea; Limperopoulos, Catherine; Roulet-Perez, Eliane; Wolf, Nicole I; Rauscher, Christian; Prayer, Daniela; Müller, Anita; Weissert, Markus; Kotzaeridou, Urania; Du Plessis, Adre J; Huisman, Thierry a G M; Boltshauser, Eugen (Developmental medicine and child neurology, 2010)
Aim Complete or subtotal absence of one cerebellar hemisphere is exceptional; only single cases have been described. We aimed to assess the long-term outcome in children with severe unilateral cerebellar hypoplasia (UCH). Method As part of a retrospective study we describe neuroimaging features, clinical findings, and cognitive outcomes of seven children with UCH (five males, two females; age at first magnetic resonance imaging [MRI]: median 1y 3mo, range 9d-8y 10mo; age at latest follow-up: median 6y 6mo, range 2y 3mo-14y 11mo). Results One child had abnormalities on prenatal MRI at 21 weeks’ gestation. The left cerebellar hemisphere was affected in five children, and the right hemisphere in two children. The vermis was involved in five children. The volume of the posterior fossa was variable. At the latest follow-up, neurological findings included truncal ataxia and muscular hypotonia in five children, limb ataxia in three patients, and head nodding in two patients. Three children had learning disability*, five had speech and language disorders, and one had a severe behavioural disorder. Interpretation Severe UCH is a residual change after a disruptive prenatal cerebellar insult, most likely haemorrhagic. The outcome is variable, ranging from almost normal development to marked developmental impairment. Ataxia is a frequent but not a leading sign. It seems that involvement of the cerebellar vermis is often, but not consistently, associated with a poorer cognitive outcome, whereas an intact vermis is associated with normal outcome and no truncal ataxia.
Online veröffentlicht 23. Oktober 2009
Gesehen am 05.05.2023